Graduated compression stockings for runners: friend, foe, or fake? - Bovenschen, H. J.; te Booij, M.; van der Vleuten, C. J. M. (Journal of Athletic Training, 2013)
Objective: To assess the effect of graduated compression stockings (GCS) on lower leg volume and leg complaints in runners during and after exercise. Design: Cross-sectional study. Setting: Radboud University Nijmegen Medical Centre and an outdoor running track in Nijmegen, The Netherlands. Patients or Other Participants: Thirteen Dutch trained recreational runners. Intervention(s): Participants used a GCS on 1 leg during running. Main Outcome Measures: (1) Lower leg volume of both legs was measured at baseline, directly after running, and at 5 minutes and 30 minutes after running using a validated perometer. (2) Leg complaints were reported on questionnaires at set intervals. Results: (1) In both experiments, the legs with GCS showed a reduction in mean (± SEM) leg volume directly after running, as compared with the leg without GCS: -14.1 ± 7.6 mL (P = .04) for the 10-km running track and -53.5 ± 17.8 mL (P = .03) for the maximum exercise test. This effect was not observed at 5 and 30 minutes after running. (2) No differences in leg complaints were reported in either experiment. Conclusions: The GCS prevented an increase in leg volume just after the running exercise. However, this result was not accompanied by a reduction in subjective questionnaire-reported leg complaints. The practical consequences of the present findings need further study.